The healthcare burden of disease progression in medicare patients with functional mitral regurgitation. (2nd September 2019) - McCullough, Peter A.; Mehta, Hirsch S.; Cork, David P.; Barker, Colin M.; Gunnarsson, Candace; Mollenkopf, Sarah; Van Houten, Joanna; Verta, Patrick
Abstract: Objective: This retrospective database analysis estimated the incremental effect that disease progression from non-clinically significant functional mitral regurgitation (nsFMR) to clinically significant FMR (sFMR) has on clinical outcomes and costs. Methods: Medicare Fee for Service beneficiaries with nsFMR were examined, defined as those with a heart failure diagnosis prior to MR. Patients were classified as ischemic if there was a history of: CAD, AMI, PCI, or CABG. The primary outcome was time to sFMR, defined as pulmonary hypertension, atrial fibrillation, mitral valve surgery, serial echocardiography, or death, using a Cox hazard regression model. Annualized hospitalizations, inpatient hospital days, and healthcare expenditures were also modeled. Results: Patients with IHD had higher risk (Hazard Ratio = 1.22 [1.14–1.30]) for disease progression compared to patients without. The progression cohort had significantly more annual inpatient hospitalizations (non-IHD = 1.32; IHD = 1.40) than the non-progression cohort (non-IHD = 0.36; IHD = 0.34), and significantly more annual inpatient hospital days (non-IHD = 13.07; IHD = 13.52) than the non-progression cohort (non-IHD = 2.29; with IHD = 2.08). The progression cohort had over 3.5-times higher costs vs the non-progression cohort, independent of IHD (non-IHD = 12, 798 vs 46, 784; IHD = 12, 582 vs 49, 348). Conclusion: Treating FMR patients earlier in their clinical trajectory may prevent disease progression and reduce high rates of healthcare utilization and expenditures.